2018
DOI: 10.1167/iovs.17-22992
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Fluorescent Mgp Transgenic Mouse for Angiogenesis and Glaucoma Longitudinal Studies

Abstract: PurposeOur goal was to generate and characterize a new mouse model in which only angiogenesis- and glaucoma-relevant tissues would be naturally fluorescent. The Matrix Gla (MGP) gene is highly expressed in vascular smooth muscle cells (VSMC) and trabecular meshwork (TM). We sought to direct our Mgp-Cre.KI mouse recombinase to VSMC/TM cells to produce their longitudinal fluorescent profiles.MethodsHomozygous Mgp-Cre.KI mice were crossed with Ai9 homozygous reporter mice harboring a loxP-flanked STOP cassette pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Our key finding was that even with multiple adjustments applied CRAE and AVR at follow-up were smaller with higher circulating levels of dp-ucMGP at baseline. Our findings are compatible with studies showing expression of MGP in capillaries and small arterioles 15 and in particular in the glaucoma-relevant tissues of the eye and the retinal microvasculature 16 – 20 . Our findings underscore the pivotal role of activated MGP in maintaining ocular homeostasis and are in line with our previous report, which showed that high dp-ucMGP predicted adverse health outcomes, including total, non-cancer and cardiovascular mortality in 2318 FLEMENGHO participants followed up for a median of 14.1 years 11 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our key finding was that even with multiple adjustments applied CRAE and AVR at follow-up were smaller with higher circulating levels of dp-ucMGP at baseline. Our findings are compatible with studies showing expression of MGP in capillaries and small arterioles 15 and in particular in the glaucoma-relevant tissues of the eye and the retinal microvasculature 16 – 20 . Our findings underscore the pivotal role of activated MGP in maintaining ocular homeostasis and are in line with our previous report, which showed that high dp-ucMGP predicted adverse health outcomes, including total, non-cancer and cardiovascular mortality in 2318 FLEMENGHO participants followed up for a median of 14.1 years 11 .…”
Section: Discussionsupporting
confidence: 93%
“…A novel MGP transgenic mouse model allows visualising angiogenesis- and glaucoma-relevant tissues by natural fluorescence 20 . These mice have normal intra-ocular pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Released active MGP acts as a local inhibitor of calcification [233,234]. MGP is also ubiquitously expressed in multiple organs, and it is likely that this widespread expression of MGP has considerably more functions than are known for local inhibitor of calcification [235][236][237][238][239]. Recently, plasma dephospho-uncarboxylated MGP (dp-ucMGP) is used as a biomarker reflecting pool vitamin K status.…”
Section: Matrix Gla Protein (Mgp)mentioning
confidence: 99%